ANALISIS KEANDALAN SISTEM PADA PENYULANG SABA SETELAH REKONFIGURASI - Ramachandra, Surya; Rinas, I Wayan; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUM, 2020)
The Saba feeder is one of the feeders located in the PLN working area of the East Bali Area, which is located around the villages of Saba, Blahbatuh and Blangsinga in the district of Gianyar. This feeder has 75 transformers with a capacity of 25-500 kVA that are connected by SUTM, SKUTM, MVTIC and ground cable lines. The reliability of the system in the Saba Feeder in the condition before being reconfigured, with a SAIFI value of 3.02 interruptions in one year, the SAIDI value is 9.28 hours per year, while for the CAIDI value is 3.24 hours per one time, which is not caused by maintenance. PT. PLN Persero regulated in SPLN No. 59 of 1985 and the target of PT. PLN PERSERO to achieve WCC or World Class Company standards, namely the value of SAIFI 3 times interruption in one year, SAIDI 3 hours of interruption in one year and CAIDI value of a maximum of 3 hours of non-availability of electricity to customers. So the value of SAIFI Penyaba Saba before reconfiguration is in accordance with PLN standards, while the value of SAIDI and CAIDI Penyaba Saba conditions before reconfiguration is still outside the PLN standard to achieve WCC. Therefore, a network reconfiguration was done to improve the SAIDI and CAIDI values in the Saba Feeder to conform to SPLN No.59 of 1985. After the network reconfiguration of the Saba feeder, changes in the SAIFI value, SAIDI and CAIDI on the Saba Feeder could improve, with the SAIFI value namely 2.73 disturbances per year, SAIDI value of 2.98 hours per year and CAIDI value of 1.08 hours per customer, so the reliability value in the Saba Feeder can be said to be reliable because it is in accordance with SPLN No. 59 of 1985.